Changes in the chronic and postprandial blood lipid profiles of trained competitive cyclists and triathletes following a ketogenic diet: a randomized crossover trial - Graybeal, A. J.; Kreutzer, A.; Moss, K.; Shah, M. (BMC Sports Science, Medicine and Rehabilitation, 2024)
Background The ketogenic diet (KD) is the most popular carbohydrate restriction strategy for endurance athletes. However, because the primary goal of employing the KD is to gain a competitive advantage in competition, endurance athletes may be less concerned with the influence of the KD on their cardiometabolic health; particularly their blood lipid profiles. Thus, the purpose of this study was to examine the chronic and postprandial blood lipid alterations following a two-week ad libitum KD compared to an ad libitum high-carbohydrate diet (HCD) and the athletes` habitual diet (HD) in a group of trained competitive cyclists and triathletes.